1994
DOI: 10.1029/93pa03501
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Pacific sea surface temperature since 1600 A.D.: The δ18O record of climate variability in Galápagos Corals

Abstract: We measured stable oxygen isotope ratios and skeletal growth rates in the massive corals Pavona clavus and P. gigantea from the west coast of Isabela Island, Galápagos, to assess interannual to decadal climate variability in the eastern Pacific. Comparisons of instrumental data sets show that sea surface temperatures (SST) in the Galápagos region are representative of a broad portion of the eastern equatorial Pacific. The site is especially well‐suited for long‐term studies of the El Niño/Southern Oscillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
220
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 382 publications
(243 citation statements)
references
References 64 publications
17
220
1
3
Order By: Relevance
“…A similar conclusion was obtained from analysis of a long temperature time series fi'om central England [Allen and Smith, 1996]. It may turn out that other cited significant decadal peaks [Dunbar et al, 1994] will also not meet this more stringent criteria. All of the above leads us to propose that the stochastic mechanism should be taken as a null hypothesis for decadal ENSO modulation against which competing mechanisms must be compared.…”
Section: Discussionsupporting
confidence: 52%
“…A similar conclusion was obtained from analysis of a long temperature time series fi'om central England [Allen and Smith, 1996]. It may turn out that other cited significant decadal peaks [Dunbar et al, 1994] will also not meet this more stringent criteria. All of the above leads us to propose that the stochastic mechanism should be taken as a null hypothesis for decadal ENSO modulation against which competing mechanisms must be compared.…”
Section: Discussionsupporting
confidence: 52%
“…It is notable that while the geochemical records from 10AR2 are closely correlated with annual growth rates, they still record climatic change well, which suggests that the climatic significance of faster and steadier growing coral is independent of skeletal growth rate (Mitsuguchi et al 2003;Jones et al 2009). Therefore, such annual resolution coral records offer a potential approach to reconstructing past climate change (Dunbar et al 1994;Cole et al 2000;Zinke et al 2014). This is especially the case for research into climate change (2002) and Wei et al (2007) over long timescales, in which annual resolution sampling can save much time and expense, but still provides similar information to studies based on high-resolution sampling.…”
Section: Climatic Significance Of the Annual Resolution Coral Recordsmentioning
confidence: 99%
“…Nevertheless, relative to the large quantity of high-resolution studies, annual to multi-year resolution coral-based studies are still relatively rare. In addition, of those coral-based studies undertaken at annual to pent-annual resolutions (Dunbar et al 1994;Cole et al 2000;Hendy et al 2002;Pelejero et al 2005;Calvo et al 2007;Linsley et al 2008;Abram et al 2009;Wei et al 2009;Deng et al 2013;Zinke et al 2014), few have focused on the replication of the lowresolution geochemical records of multiple coral cores. Some studies have evaluated the climatic significance of annual coral records averaged using monthly or sub-annual values from each year (Lough 2004;Smith et al 2006;Pfeiffer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Scleractinian corals can live for hundreds of years and continuously record changes in the marine environment in their aragonitic skeletons. Annual density banding in corals allows accurate time control on reconstructions (Knutson et al, 1972), and many studies have utilized corals for paleoclimatic and paleoenvironmental reconstruction, measuring stable isotopes (Dunbar et al, 1994;Cobb et al, 2003, Marion et al, 2005 and metals that substitute into the CaCO 3 matrix (Smith et al, 1979;Hanna and Muir, 1990;Bastidas and Garcia, 1999;Fallon et al, 2002;David, 2003;McCulloch et al, 2003;Ramos et al, 2004;Fleitmann et al, 2007;Lewis et al, 2007;Prouty et al, 2008). Although the coral calcification mechanism and therefore the exact pathway of metal substitution in the aragonite matrix are still under debate (Cohen and McConnaughey, 2003), empirical studies have shown that corals appear to faithfully record relative metal concentrations in the surrounding seawater (Runnalls and Coleman, 2003;Correge, 2006).…”
Section: Introductionmentioning
confidence: 99%